Odpowiedzi

2009-11-20T22:46:17+01:00
Y = ax + b
I) 5 =-a + b ----> b = 5 + a
II ) -4 = 2a + b
-----------------
od I odejmujemy II
9 = -3a
a = 9 :(-3) = -3
b = 5 +(-3) = 2
--------------------
y = -3x +2
f(-4) = -3(-4) +2 = 12 +2 =14
f(3) = -3*3 + 2 = -9 +2 = - 7
f(-8/3) = -3(-8/3) + 2 = 8 + 2 = 10
-3 = -3x +2
3x =3+2 = 5
x = 5/3
Czyli dla x =5/3 , y =-3
-10 = -3x +2
3x = 2+10 = 12
x = 12:3 = 4
czyli dla x =4, y = -10
Wpisz sobie do tabelki.
Najlepsza Odpowiedź!
2009-11-20T22:50:34+01:00
X -4 -5/3 -1 2 3 4 -8/3
f(x) 14 -3 5 -4 -7 -10 10